2010
DOI: 10.1016/j.neuron.2010.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial EEG Correlates of Expectancy and Memory Formation in the Human Hippocampus and Nucleus Accumbens

Abstract: The human brain is adept at anticipating upcoming events, but in a rapidly changing world, it is essential to detect and encode events that violate these expectancies. Unexpected events are more likely to be remembered than predictable events, but the underlying neural mechanisms for these effects remain unclear. We report intracranial EEG recordings from the hippocampus of epilepsy patients, and from the nucleus accumbens of depression patients. We found that unexpected stimuli enhance an early (187 ms) and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
175
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 167 publications
(193 citation statements)
references
References 75 publications
15
175
1
2
Order By: Relevance
“…In either case, there may be a direct relationship between hippocampal mismatch detection and the disambiguation of similar stimuli. One caveat, however, in relating the present findings to prior evidence of hippocampal disambiguation of similar events (Bakker et al, 2008;Hulbert and Norman, 2015;Favila et al, 2016) is that our near condition only referred to stimuli from a common visual category, whereas prior studies have considered stimuli with much stronger perceptual overlap. Therefore, an informative follow-up to the present work would be to consider the relationship between prediction strength and hippocampal outcome responses across a wider range of similarities between predictions and outcomes (Lacy et al, 2011;Duncan et al, 2012).…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations
“…In either case, there may be a direct relationship between hippocampal mismatch detection and the disambiguation of similar stimuli. One caveat, however, in relating the present findings to prior evidence of hippocampal disambiguation of similar events (Bakker et al, 2008;Hulbert and Norman, 2015;Favila et al, 2016) is that our near condition only referred to stimuli from a common visual category, whereas prior studies have considered stimuli with much stronger perceptual overlap. Therefore, an informative follow-up to the present work would be to consider the relationship between prediction strength and hippocampal outcome responses across a wider range of similarities between predictions and outcomes (Lacy et al, 2011;Duncan et al, 2012).…”
Section: Discussionmentioning
confidence: 56%
“…However, for the comparison of near versus far trials, a cluster was observed in hippocampus, but not IFG or caudate. Likewise, the comparison of near versus far trials did not reveal clusters in the ventral striatum, midbrain, or insula, regions that have been associated previously with prediction error, mismatch, and/or expectancy violation signals (Berns et al, 2001;Lisman and Grace, 2005;D'Ardenne et al, 2008;Preuschoff et al, 2008;Axmacher et al, 2010).…”
Section: Outcome Responses In Frontostriatal Regionsmentioning
confidence: 62%
See 2 more Smart Citations
“…The time interval ranging from 0 to 1000 ms after stimulus onset is sufficient to capture the main ERP components (hippocampus: a positive peak at around 200 ms and a negative peak at around 500 ms; rhinal cortex: a negative peak at around 400 ms) that have been described in previous studies [46,47]. We observe here similar ERP components, and the clear amplitude differences seen for the different conditions already indicate that the rhinal cortex and the hippocampus are involved in the memory processing steps investigated here.…”
Section: Detection Of Transient Directional Couplings In Event-relatementioning
confidence: 96%